EMS decoding algorithm that introduced shuffled strategy and improved variable node update - Cao, Xiawei; Ji, Yuanfa; Sun, Xiyan; Liang, Weibin; Kamarul Hawari, Ghazali (Institute of Electrical and Electronics Engineers Inc., 2022)
Non-binary LDPC codes have excellent performance, but the decoding algorithm is complex. EMS algorithm reduces the search space of the check equation by truncating the iterative message vector, and exchanges performance for lower complexity. In this paper, we propose an EMS decoding algorithm (Shuffled_VNU_EMS) with a shuffled strategy and improved variable node update. This algorithm updates by column, so that the latest variable node information of the last column can be used. At the same time, to reduce the information oscillation, a weighting factor ß is introduced when updating the variable node information,ß= 0.9. The simulation results show that when the code length is 512, the code rate is 0.5 and the bit error rate is 10-4, the coding gain of the shuffled VNU EMS algorithm proposed in this paper is 0.18 dB higher than that of the classical EMS algorithm.